If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-60=-3(-4)m
We move all terms to the left:
-60-(-3(-4)m)=0
We calculate terms in parentheses: -(-3(-4)m), so:We move all terms containing m to the left, all other terms to the right
-3(-4)m
We multiply parentheses
12m
Back to the equation:
-(12m)
-12m=60
m=60/-12
m=-5
| 6n-2+3n=16 | | 2(s-5)=2(5+5) | | -7w=16+-2 | | 4.5t-13.5-2.7=15.3 | | 7x-2x+8+1=74 | | 2y-4y=34-18 | | (32x)=256 | | 7=777777x765456785456786789 | | -11(x-6)=-60 | | 2(4x+1)−2x=9x−1 | | 256=32x | | 9x-116=180 | | 500+2.50x=775 | | 9+3x+7x-x=72 | | 6c-3c=-27 | | 2.50+3h=$13 | | 7=7x−21 | | -8=r-2-8 | | -9x-4+6x=-6x+5-7 | | (8x^2+52x-28)/4=0 | | 6-3x=-5x+11x+33 | | x2−4x=12 | | 4x2-17=-1 | | 7=74n(8) | | x*0.6=18 | | 7+⅔x=-1 | | 4p-16+6=10 | | 3(2+5m)-10=-22+6 | | 10+b/6=11 | | 9x+121=180 | | 2(0)-5=x | | -5x-1/3(9x+42)+70=0 |